Analysis of the Practice of the Ijon System from the Perspective of Islamic Economic Law for Rice Farmers in Sugih Waras Village, Teluk Gelam District, Ogan Komering Ilir Regency - Setiawan, Bagus; Astina, Ria; Pramita, Cindi (Sean Institute, 2025)
The practice of ijonis a phenomenon is still common in rural areas, including in Sugih Waras Village, Teluk Gelam District. This system is used by rice farmers to obtain quick funds before the harvest by selling unharvested crops to middlemen at prices lower than the market price. This study aims to analyze the mechanism of the bonded debt system in Sugih Waras Village and examine its compliance with the principles of Islamic economic law. The research method used is a qualitative approach. The results indicate that the ijon system is carried out due to limited capital and difficult access for farmers. From the perspective of Islamic economic law, this practice does not fully meet the requirements of a valid sale and purchase agreement because the object of the transaction (the harvest) is still gharar (unclear quantity and quality) and there are elements of price exploitation that are detrimental to farmers. This study recommends alternative sharia financing such as salam, mudharabah, or musyarakah contracts that are fairer and in accordance with sharia principles. It is hoped that the results of this study can be used as a consideration for the community and policymakers in formulating more equitable agricultural financing solutions.